Halal value creation: its role in adding value and enabling logistics service. Issue 9 (3rd July 2016) - Karia, Noorliza; Asaari, Muhammad Hasmi Abu Hassan
Abstract: The need to implement halal value creation into logistics and supply chains has been recognised recently. Yet, there is a lack of efforts to leverage resources and capabilities in contributing to the halal value creation for competitive advantage and subsequently firm performance. The purpose of this paper is to understand the halal value creation of current practices and its role in adding value and enabling logistics service. A structure interview of seven third-party logistics (3PL) providers is conducted to provide more precise perception about works by viewing with the lens prescribed by practitioners rather than reviews. The results draw the novel practices of halal value creation in logistics, that have not been revealed and further identifies five emerging resources of 'resource-based halal logistics'. These create innovation capability (ability to launch successful halal goods/services) in logistics services, which are transformed into benefits of profits for 3PLs and value for customers.